Are we ready yetn ; Memories of war ; The Tops!!! - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Are We Ready Yet presents the problems in Bacolor and Porac, Pampanga after four years since the eruption of Mt. Pinatubo. The personal recollections of war veterans during the World War II is what Memories of war all about. The Tops presented the ten outstanding students of the Philippines.
Are we ready yetn (17 min.) -- Memories of war (15 min.) -- The tops (18 min.)
VHS.
Keywords: Pinatubo, Mount (Zambales).; World War, 1939-1945 -- Personal narratives; Students -- Awards